A Comparison of linear and non-Linear regression to study the effect of a supply chain agility on competitive advantage An analytical study - Gabrow, Raghad Yousif; j. skukri, Abdulhakim; Alobaidi, Muthanna (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to explain the importance of Agility in supply chains and how it is critical for competitive advantage. The study proved that the agility supply chain helps the company to explore and exploit opportunities in fast changing markets.